2021
DOI: 10.1038/s41598-021-95281-3
|View full text |Cite
|
Sign up to set email alerts
|

Opposing shifts in distributions of chlorophyll concentration and composition in grassland under warming

Abstract: Global warming has significantly altered the distribution and productivity of vegetation owing to shifts in plant functional traits. However, chlorophyll adaptations—good representative of plant production—in grasslands have not been investigated on a large scale, hindering ecological predictions of climate change. Three grassland transects with a natural temperature gradient were designed in the Tibetan, Mongolian, and Loess Plateau to describe the changes in chlorophyll under different warming scenarios for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Chl and carotenoids are indirect biochemical indicators of photosynthetic activity [85]. The chl a/b ratio is expected to increase when the leaf N content decreases [86,87].…”
Section: Discussionmentioning
confidence: 99%
“…Chl and carotenoids are indirect biochemical indicators of photosynthetic activity [85]. The chl a/b ratio is expected to increase when the leaf N content decreases [86,87].…”
Section: Discussionmentioning
confidence: 99%
“…The original plant images obtained in the experiment have a high resolution and large storage capacity, but most of the information is redundant, which will reduce the efficiency and accuracy of plant 3D point cloud reconstruction. In order to eliminate irrelevant information, such as background and ground, this study plans to perform image pre-processing as shown in Figure 2 3) is utilized to overlay the noise-reduced image (6) mask, resulting in the mask image (7). The size of an individual image in this process ranges from 0.7 to 0.9 MB.…”
Section: Image Pre-processingmentioning
confidence: 99%
“…The control checks (CK) group model shown in picture (5), sufficient water conditions provide plants with energy for photosynthesis. The plant maintains normal growth status, and chlorophyll is still distributed gradually from top to bottom among the poplar trees; in the severe drought group shown in picture (7), severe water shortage in the plants caused the leaves to wilt and turn yellow, increase the inclination angle in a short period of time, limit photosynthesis, some leaves have fallen off, and the overall chlorophyll content dropped sharply. But at the same time, from picture (6) combined with the analysis results in Figure 10, the consistent point between severe drought and mild drought is that the upper leaves of the four varieties of poplar trees still have slightly increased values, and the elevated value in the mild drought group was greater than that in the severe drought group.…”
Section: Visualization Of 3d Distribution Of Poplar Chlorophyllmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorophyll plays a pivotal role in the photosynthesis process by transferring the energy of photons to the reaction center of PSII (Taiz and Zeiger 2010). In general, chlorophyll content can reflect the amount of photon energy absorbed per unit area and is a well-known indicator of physiological characteristics such as plant productivity (Anderson 1967;Zhang et al 2021). Measurements of chlorophyll content over the season showed that R. rugosa in the Goraebul coastal dunes had higher chlorophyll a and carotenoid content, while there was no significant difference between the two habitats for chlorophyll b (Fig.…”
Section: Chlorophyll Contentmentioning
confidence: 99%